The role of Th/Treg immune cells in osteoarthritis - Wen, Zhi; Qiu, Liguo; Ye, Zifeng; Tan, Xuyi; Xu, Xiaotong; Lu, Min; Kuang, Gaoyan (Frontiers in Immunology, 2024)
Osteoarthritis (OA) is a prevalent clinical condition affecting the entire joint, characterized by its multifactorial etiology and complex pathophysiology. The onset of OA is linked to inflammatory mediators produced by the synovium, cartilage, and subchondral bone, all of which are closely tied to cartilage degradation.Consequently, OA may also be viewed as a systemic inflammatory disorder. Emerging studies have underscored the significance of T cells in the development of OA. Notably, imbalances in Th1/Th2 and Th17/Treg immune cells may play a crucial role in the pathogenesis of OA. This review aims to compile recent advancements in understanding the role of T cells and their Th/Treg subsets in OA, examines the immune alterations and contributions of Th/Treg cells to OA progression, and proposes novel directions for future research, including potential therapeutic strategies for OA.